Optimization of External Disintegrating Materials in Wet Granulation Formulation of Ondansetron Tablets - Permana, Yandi; Tuba, Syahrul; Riyadi, Taufik; Sugindro, Sugindro (Pharmaceutical Sciences and Research, 2024)
Inadequate management of chemotherapy-induced side effects, including nausea and vomiting, can impact the healing response of cancer patients. Ondansetron, a preferred medication for the treatment, is classified as a biopharmaceutic classification system (BCS) class II drug, which limits its bioavailability. To enhance its solubility, sodium starch glycolate (SSG) and pregelatinized starch (PG) are used as super disintegrants. This study investigates the impact of these super disintegrants on ondansetron dissolution and identifies the optimal formulation. Ondansetron tablets were prepared using the wet granulation method, with nine formulations varying in SSG and PG concentrations (0%, 1%, 3%, 5%, and 7%). The tablets underwent physical and chemical quality evaluations. The results indicate that ondansetron dissolution improved with SSG and PG at concentrations of 1% and 3% but decreased at higher concentrations (5% and 7%). Statistical analysis revealed significant differences in dissolution fraction parameters and efficiency across varying SSG and PG concentrations (p < 0.05). The optimal formulation for enhancing ondansetron dissolution was found to be with 3% PG, achieving a dissolution efficiency value of 79.88% + 0.11%.